2016
DOI: 10.2196/resprot.5122
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Patient Portal Preferences and Health Literacy: A Survey Using Crowdsourcing

Abstract: BackgroundeHealth apps have the potential to meet the information needs of patient populations and improve health literacy rates. However, little work has been done to document perceived usability of portals and health literacy of specific topics.ObjectiveOur aim was to establish a baseline of lung cancer health literacy and perceived portal usability.MethodsA survey based on previously validated instruments was used to assess a baseline of patient portal usability and health literacy within the domain of lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…Because Mechanical Turk has been shown to produce data quickly and at a low cost, it has been used extensively to conduct health research. [ 15 26 ] It is therefore important to understand any biases within and the external validity of this population. This study found that Turkers were generally younger, of lower socioeconomic status, and less racially/ethnically diverse than the national population.…”
Section: Discussionmentioning
confidence: 99%
“…Because Mechanical Turk has been shown to produce data quickly and at a low cost, it has been used extensively to conduct health research. [ 15 26 ] It is therefore important to understand any biases within and the external validity of this population. This study found that Turkers were generally younger, of lower socioeconomic status, and less racially/ethnically diverse than the national population.…”
Section: Discussionmentioning
confidence: 99%
“…They also serve as a 2‐way communication tool that allows patients to report to their care providers any unresolved or new symptoms and request medication refills, whereas the providers can answer patients' questions and send reminders of preventive screening tests and vaccinations, scheduled procedures or studies, and upcoming outpatient appointments. One survey showed a trend of chronically ill patients having a more positive view of patient portals [41], but more studies are required to prove their value in enhancing patient communication, education and empowerment, and their potential in reducing miscommunication and unnecessary patient visits.…”
Section: Current Statementioning
confidence: 99%
“…Zide M, et al 2016 [45] The effect of patient health literacy in radiology on perceived portal usability.…”
Section: Yes Data Analysis 1670 Doctors and Non-doctorsmentioning
confidence: 99%